Polyester-based degradable plastic engineering particles and preparation method thereof
Patent Information
- Application Number
- CN202611003356.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-07
- Publication Date
- 2026-10-16
AI Technical Summary
该方式虽然能够在一定程度上改善材料性能,但亲水降解组分在造粒、储存和二次熔融成型过程中容易引入水分并形成界面缺陷,导致聚酯链段提前水解和熔体性能波动
[0031](1)本发明通过聚酯类可降解树脂、工程支撑组分、热史响应型潜伏降解颗粒、相容调控组分和链扩调控组分形成工程颗粒,并在热史响应型潜伏降解颗粒中设置亲水可降解芯材、固相破界层和熔体剪切缓冲层,使工程颗粒在加工阶段保持壳层完整,在废弃固相破碎阶段暴露亲水可降解芯材,从而兼顾二次熔融成型稳定性和废弃后降解启动性,相较于现有单纯依靠聚酯共混、填料增强和普通亲水组分共混的可降解塑料,本发明能够进一步提高工程颗粒在全生命周期中的性能协调性。
Smart Images

Figure CN122917501A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of biodegradable polymer materials technology, and in particular to an engineered particle of polyester biodegradable plastic and its preparation method. Background Technology
[0002] Polyester biodegradable plastics are widely used in packaging, sheets, blister packaging, injection molding parts and disposable structural products due to their good processing adaptability and environmental degradation potential. In order to meet the requirements of engineering use, it is usually necessary to add engineering support components, compatibility control components, chain expansion control components and hydrophilic degradable components such as starch and cellulose to the polyester matrix to improve the strength, dimensional stability, melt processability and post-disposal degradation performance of the material.
[0003] However, engineered granules of biodegradable polyester plastics are usually not the final product, but rather require storage, transportation, and downstream secondary melt molding to form the actual usable product. Current technologies often balance enhancement and degradation performance through formulation blending, frequently dispersing the engineering support component and the hydrophilic degradable component together within the continuous polyester phase. While this approach can improve material properties to some extent, the hydrophilic degradable component easily introduces moisture and forms interfacial defects during granulation, storage, and secondary melt molding, leading to premature hydrolysis of polyester segments and fluctuations in melt properties. If the hydrophilic degradable component is isolated using ordinary coating methods, it may prevent moisture from entering after disposal, causing a delay in the degradation initiation process.
[0004] Therefore, how to ensure the stability of engineered particles during the processing stage, maintain their load-bearing performance during service, and effectively activate the degradation channel after the waste solid phase is crushed has become a technical problem that needs to be solved in the engineering application of polyester biodegradable plastics. Summary of the Invention
[0005] This invention overcomes the shortcomings of the prior art and provides an engineering particle of polyester biodegradable plastic and its preparation method.
[0006] To achieve the above objectives, the technical solution adopted by the present invention is as follows: an engineering granule of polyester biodegradable plastic, comprising the following components by weight:
[0007] 100 parts of biodegradable polyester resin;
[0008] The engineering support components consist of 5 to 35 parts;
[0009] 3–25 parts of thermally history-responsive latent degradation particles;
[0010] 0.5–8 parts of compatibility-regulating components;
[0011] Chain expansion regulating component: 0.05–3 parts;
[0012] The thermal history-responsive latent degradation particles include a hydrophilic degradable core material, a solid-phase boundary-breaking layer covering the outside of the hydrophilic degradable core material, and a melt shear buffer layer covering the outside of the solid-phase boundary-breaking layer.
[0013] The melt shear buffer layer has deformation buffering properties at the melt processing temperature of the polyester biodegradable resin, so that the solid phase breaking layer remains unbroken during melt granulation and secondary melt molding.
[0014] The solid-phase boundary breaking layer forms a boundary opening after solid-phase crushing treatment, exposing the hydrophilic and biodegradable core material at the fracture surface.
[0015] Both the engineering support component and the thermal history-responsive latent degradable particles are dispersed in the continuous phase formed by the polyester biodegradable resin, and in the cross section of the engineering particles, the direct contact area between the engineering support component and the thermal history-responsive latent degradable particles accounts for 0 to 20% of the outer surface area of the thermal history-responsive latent degradable particles.
[0016] In a preferred embodiment of the present invention, the polyester biodegradable resin includes at least two of polylactic acid, polybutylene adipate terephthalate, polybutylene succinate, and polyhydroxyalkanoates; by weight, the polyester biodegradable resin includes 40-75 parts of polylactic acid, 15-45 parts of polybutylene adipate terephthalate, and 5-30 parts of at least one of polybutylene succinate and polyhydroxyalkanoates.
[0017] In a preferred embodiment of the present invention, the engineering support component includes at least one of talc, calcium carbonate, wollastonite, silica, montmorillonite, glass micron powder, and plant ash. The average particle size of the engineering support component is 0.5 to 15 μm, and the surface of the engineering support component has at least one of a silane coupling layer, a titanate coupling layer, an aluminate coupling layer, and a polyester oligomer compatibility layer.
[0018] In a preferred embodiment of the present invention, the hydrophilic biodegradable core material includes at least one of starch, cellulose, hemicellulose, lignocellulose, porous plant fiber particles and biodegradable low polyester, and the average particle size of the hydrophilic biodegradable core material is 5 to 80 μm.
[0019] In a preferred embodiment of the present invention, the solid-phase boundary layer comprises at least one of a brittle polyester microlayer, a biodegradable layer containing mineral flakes, and a hydrolyzable brittle oligomer layer, wherein the thickness of the solid-phase boundary layer is 0.2–5 μm.
[0020] In a preferred embodiment of the present invention, the melt shear buffer layer comprises at least one of a flexible aliphatic polyester layer, a polyester grafted compatibility layer, and a biodegradable elastic phase layer. The thickness of the melt shear buffer layer is 0.5–8 μm, and the softening temperature of the melt shear buffer layer is 5–35°C lower than that of the solid phase breaking layer.
[0021] In a preferred embodiment of the present invention, after the engineering particles are melt-blended, the shell penetration damage rate of the thermally responsive latent degradable particles is 0-8%; after the product obtained by the engineering particles through secondary melt molding is subjected to solid-phase crushing treatment, the exposure ratio of the hydrophilic degradable core material on the crushed cross-section is 20%-60%.
[0022] In a preferred embodiment of the present invention, the compatibility regulating component includes at least one of maleic anhydride grafted polyester, epoxy functionalized compatibilizer, isocyanate functionalized compatibilizer, and polyester oligomer compatibilizer; the chain extension regulating component includes at least one of polyfunctional epoxy chain extender, carbodiimide chain extender, isocyanate chain extender, and acid anhydride chain extender.
[0023] A method for preparing polyester biodegradable plastic engineering granules includes the following steps:
[0024] S1. Prepare thermal history-responsive latent degradation particles, wherein the thermal history-responsive latent degradation particles include a hydrophilic degradable core material, a solid-phase boundary layer and a melt shear buffer layer, and the average particle size of the thermal history-responsive latent degradation particles is 10-120 μm.
[0025] S2. Add the biodegradable polyester resin, engineering support component, compatibility control component and chain expansion control component to the front end of the extrusion equipment for melt compounding to form a continuous polyester melt containing the engineering support component;
[0026] S3. After the continuous polyester melt is formed, the thermal history-responsive latent degradation particles are added to the later stage of the extrusion equipment.
[0027] S4. Control the mixing intensity in the later stage of the extrusion equipment so that the thermal history-responsive latent degradation particles are dispersed in the continuous polyester melt, and the solid phase boundary layer remains unbroken during the melt mixing process.
[0028] S5. After degassing, extrusion, cooling and pelletizing, the engineered granules of the polyester biodegradable plastic are obtained.
[0029] In a preferred embodiment of the present invention, in step S2, the temperature of the front section of the extrusion equipment is 150–210°C, and the screw speed is 150–450 r / min; in step S3, the thermal history-responsive latent degradation particles are added to the middle and rear sections of the extrusion equipment via side feeding; in step S4, the unit mass mechanical energy input of the middle and rear sections of the extrusion equipment is 35%–85% of the unit mass mechanical energy input of the front section of the extrusion equipment, the agglomerate size of the thermal history-responsive latent degradation particles is 20–200 μm, and the shell penetration breakage rate of the thermal history-responsive latent degradation particles after melt mixing is 0–8%; after step S5, a dehumidification and crystallization shaping step is further included, wherein the dehumidification and crystallization shaping step is: treating the granulated engineered particles at 45–85°C for 0.5–6 h to make the moisture content of the engineered particles 100–800 ppm.
[0030] This invention addresses the shortcomings of the prior art and has the following beneficial effects:
[0031] (1) The present invention forms engineered particles by using polyester biodegradable resin, engineering support components, thermal history-responsive latent degradable particles, compatibility control components and chain expansion control components. A hydrophilic biodegradable core material, a solid phase breaking layer and a melt shear buffer layer are set in the thermal history-responsive latent degradable particles, so that the engineered particles maintain the integrity of the shell during the processing stage and expose the hydrophilic biodegradable core material during the waste solid phase breaking stage. This balances the stability of secondary melt molding and the degradation initiation after waste. Compared with existing biodegradable plastics that rely solely on polyester blending, filler reinforcement and ordinary hydrophilic component blending, the present invention can further improve the performance coordination of engineered particles throughout the entire life cycle.
[0032] (2) By sequentially setting a solid-phase breaking layer and a melt shear buffer layer on the outside of the hydrophilic biodegradable core material, and limiting the shell penetration damage rate of the thermal history-responsive latent degradation particles after melt mixing, the hydrophilic biodegradable core material is less likely to come into premature contact with the polyester continuous phase during granulation and secondary melt molding, thereby reducing the risk of hydrolysis and melt performance fluctuations in the processing thermal history. Compared with the existing method of directly adding hydrophilic degradation components such as starch and cellulose, the present invention can further improve the storage stability, processing stability and downstream molding consistency of the particles.
[0033] (3) This invention enables the solid phase breaking layer to form a breaking opening after solid phase crushing treatment, and makes the hydrophilic biodegradable core material form a certain exposure ratio on the broken cross section, so that the waste product can form a water entry path along the exposed core material after crushing and pyrolysis, thereby improving the degradation initiation efficiency. Compared with the existing ordinary coating filler, which relies on the gradual penetration of environmental moisture into the shell layer, this invention can transform the cross section formation process in the waste stage into degradation initiation conditions, further improving the controllability of degradation after waste of biodegradable plastics.
[0034] (4) By dispersing both the engineering support component and the thermal history-responsive latent degradation particles in a continuous phase formed by polyester biodegradable resin and limiting the direct contact area ratio between the two, the engineering support component mainly undertakes the mechanical support function, and the thermal history-responsive latent degradation particles mainly undertake the channel opening function after disposal. This reduces the weakening effect of the hydrophilic degradation component on the reinforcing interface. Compared with the existing system of random blending of reinforcing filler and degradation filler, the present invention can further achieve a synergistic improvement in engineering load-bearing performance, processing stability performance and waste degradation performance. Attached Figure Description
[0035] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0036] Figure 1 This is a flowchart of the preparation method of the present invention; Detailed Implementation
[0037] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0038] Many specific details are set forth in the following description in order to provide a full understanding of the invention. However, the invention may also be practiced in other ways different from those described herein. Therefore, the scope of protection of the invention is not limited to the specific embodiments disclosed below.
[0039] like Figure 1 As shown, the present invention discloses a method for preparing polyester biodegradable plastic engineering particles, comprising the following steps:
[0040] S1. Prepare thermal history-responsive latent degradation particles, wherein the thermal history-responsive latent degradation particles include a hydrophilic degradable core material, a solid-phase boundary layer and a melt shear buffer layer, and the average particle size of the thermal history-responsive latent degradation particles is 10 μm to 120 μm.
[0041] S2. Add the biodegradable polyester resin, engineering support component, compatibility control component and chain expansion control component to the front end of the extrusion equipment for melt compounding to form a continuous polyester melt containing the engineering support component.
[0042] S3. After the continuous polyester melt is formed, thermally responsive latent degradation particles are added to the later stage of the extrusion equipment.
[0043] S4. Control the mixing intensity in the later stages of the extrusion equipment to disperse the thermally responsive latent degradation particles in the continuous polyester melt, and to keep the solid-phase boundary layer from breaking through during the melt mixing process.
[0044] S5. After degassing, extrusion, cooling and pelletizing, engineered granules of polyester biodegradable plastic are obtained.
[0045] The core concept of this invention is to construct a hydrophilic biodegradable core material into thermally history-responsive latent degradable particles with a solid-phase boundary-breaking layer and a melt shear buffer layer. Then, a polyester biodegradable resin, an engineering support component, a compatibility control component, and a chain expansion control component are melt-composite in the front section of an extrusion device to form a continuous polyester melt. Subsequently, thermally history-responsive latent degradable particles are added in the middle and rear sections of the extrusion device in a low-damage mixing manner. This ensures that the shell of the particles remains unbroken during the granulation and secondary melting and molding stages. After the waste solid phase is broken, the boundary opening is formed through the solid-phase boundary-breaking layer, exposing the hydrophilic biodegradable core material. This simultaneously takes into account processing stability, engineering load-bearing capacity, and post-waste degradation initiation.
[0046] In step S1, thermally history-responsive latent degradable particles are prepared. These particles comprise a hydrophilic biodegradable core material, a solid-phase boundary-breaking layer coating the outside of the hydrophilic biodegradable core material, and a melt shear buffer layer coating the outside of the solid-phase boundary-breaking layer. The average particle size of the hydrophilic biodegradable core material is 5 μm to 80 μm, the thickness of the solid-phase boundary-breaking layer is 0.2 μm to 5 μm, the thickness of the melt shear buffer layer is 0.5 μm to 8 μm, and the softening temperature of the melt shear buffer layer is 5°C to 35°C lower than that of the solid-phase boundary-breaking layer. The resulting thermally history-responsive latent degradable particles have an average particle size of 10 μm to 120 μm.
[0047] Specifically, corn starch and microcrystalline cellulose were placed in a vacuum drying oven and dried at 60°C for 6 hours to reduce the moisture content of both corn starch and microcrystalline cellulose to below 800 ppm. Then, the dried corn starch and microcrystalline cellulose were added to a high-speed mixer at a mass ratio of 7:3 and mixed at 800 r / min for 8 minutes to obtain a hydrophilic biodegradable core material premix powder. The hydrophilic biodegradable core material premix powder was then graded using an airflow sieving device to collect core material particles with an average particle size of 35 μm, thus obtaining the hydrophilic biodegradable core material.
[0048] Specifically, the brittle polyester microlayer material was added to a mixed solvent of ethyl acetate and acetone, with a mass ratio of 6:4. The mixture was stirred at 25°C for 40 min at a stirring speed of 500 r / min to obtain a solid-phase boundary-breaking coating solution with a mass fraction of 8%.
[0049] The above-mentioned hydrophilic biodegradable core material is added to the material chamber of the fluidized bed bottom spray coating equipment. The inlet air temperature is controlled at 40℃, the outlet air temperature at 32℃, the atomization pressure at 0.20MPa, and the bottom spray liquid speed at 5g / min. The solid phase boundary breaking coating liquid is sprayed into the bottom of the fluidized bed, so that the brittle polyester micro-layer material is deposited on the outside of the hydrophilic biodegradable core material with the evaporation of the solvent.
[0050] After the solid-phase boundary-breaking coating liquid was sprayed in, the particles were further fluidized and dried under hot air at 40℃ for 30 min, and then dried in a vacuum drying oven at 45℃ for 3 h. Agglomerated particles were removed by vibrating screen to obtain intermediate particles with a solid-phase boundary-breaking layer. The thickness of the obtained solid-phase boundary-breaking layer was 1.6 μm.
[0051] Specifically, the flexible aliphatic polyester layer material is placed in a jacketed molten bath, and the temperature of the molten bath is controlled at 100°C, so that the flexible aliphatic polyester layer material softens into a semi-molten state.
[0052] Intermediate particles with solid-phase breaking layers are added to a roller-type melt cladding equipment. The jacket temperature is controlled at 100℃ and the roller speed is 30r / min. The semi-molten flexible aliphatic polyester layer material is added to the roller-type melt cladding equipment in 5 batches. After each addition, the material is cladding for 4 minutes. After all the material is added, the material is cladding for another 20 minutes.
[0053] After the rolling process is completed, dry air at a temperature of 28°C is introduced into the drum-type melt rolling equipment to cool and solidify the melt shear buffer layer on the particle surface.
[0054] The cooled particles were removed and depolymerized at a low speed of 80 r / min for 3 min. The particles with an average particle size of 58 μm were then collected by sieving to obtain thermally responsive latent degradation particles.
[0055] The resulting melt shear buffer layer has a thickness of 3.2 μm, a softening temperature of 65 °C, and a softening temperature of 85 °C. The softening temperature of the melt shear buffer layer is 20 °C lower than that of the solid phase breaking layer.
[0056] In S2, a polyester biodegradable resin, an engineering support component, a compatibility control component, and a chain expansion control component are added to the front end of the extrusion equipment for melt compounding.
[0057] The component comprises 100 parts of a polyester biodegradable resin, 5 to 35 parts of an engineering support component, 0.5 to 8 parts of a compatibility regulating component, and 0.05 to 3 parts of a chain extension regulating component.
[0058] The polyester biodegradable resin includes 40 to 75 parts of polylactic acid, 15 to 45 parts of polybutylene adipate terephthalate, and 5 to 30 parts of at least one of polybutylene succinate and polyhydroxyalkanoate, wherein the average particle size of the engineering support component is 0.5 μm to 15 μm.
[0059] Specifically, by weight, prepare 100 parts of polyester biodegradable resin, 20 parts of engineering support component, 3 parts of compatibility regulation component and 0.8 parts of chain expansion regulation component.
[0060] The polyester biodegradable resin is composed of 60 parts polylactic acid, 30 parts polybutylene adipate terephthalate, and 10 parts polybutylene succinate. The engineering support component is talc powder treated with silane coupling, with an average particle size of 3.2 μm. The compatibility control component is a mixture of maleic anhydride-grafted polyester and epoxy functionalized compatibility agent in a mass ratio of 2:1. The chain extension control component is a multifunctional epoxy chain extender.
[0061] Specifically, polylactic acid, polybutylene adipate terephthalate, and polybutylene succinate were placed in a dehumidifying dryer and dried at 55°C for 6 hours. Talc powder treated with silane coupling was placed in an 80°C forced-air drying oven and dried for 4 hours. The dried polylactic acid, polybutylene adipate terephthalate, polybutylene succinate, silane-coupled talc powder, compatibility control components, and chain expansion control components were added to a high-speed mixer. The speed of the high-speed mixer was controlled at 600 r / min, and the mixture was mixed for 10 minutes to obtain a premix for front-end melt composite.
[0062] Specifically, the premixed material for the front-end melt compounding is added to the main feed port of the twin-screw extruder. The twin-screw extruder is sequentially set with a front-end melt compounding zone, a middle and rear-end low-damage mixing zone, an exhaust zone, and an extrusion granulation zone along the material conveying direction. The front-end temperature of the extruder is controlled at 150°C to 210°C, and the screw speed is controlled at 150 r / min to 450 r / min.
[0063] Furthermore, the barrel temperature of the front-end melting and compounding zone is controlled sequentially at 170℃, 175℃, 180℃ and 185℃, and the screw speed is controlled at 280 r / min, so that the polyester biodegradable resin melts to form a continuous melt, and the engineering support component is dispersed in the polyester continuous melt, thus obtaining a polyester continuous melt containing the engineering support component.
[0064] In S3, after the continuous polyester melt is formed, thermally responsive latent degradation particles are added to the later stage of the extrusion equipment. The amount of thermally responsive latent degradation particles added is 3 to 25 parts.
[0065] Specifically, by weight, the amount of thermally responsive latent degradable particles added is 14 parts. The thermally responsive latent degradable particles are added to the middle and rear section of the extrusion equipment by side feeding. The barrel temperature before and after the side feed port is controlled at 168°C to 176°C, so that the thermally responsive latent degradable particles enter the already formed continuous polyester melt, avoiding premature exposure of the hydrophilic degradable core material under the strong melt shear conditions in the front section.
[0066] In S4, the mixing intensity in the middle and later stages of the extrusion equipment is controlled to disperse the thermally responsive latent degradation particles in the continuous polyester melt, and to keep the solid-phase boundary layer from breaking through during the melt mixing process. The mechanical energy input per unit mass in the middle and later stages of the extrusion equipment is 35% to 85% of the mechanical energy input per unit mass in the front stages of the extrusion equipment. The agglomerate size of the thermally responsive latent degradation particles is 20 μm to 200 μm, and the shell penetration damage rate of the thermally responsive latent degradation particles after melt mixing is 0% to 8%.
[0067] Specifically, the unit mass mechanical energy input in the low-damage mixing zone of the middle and later stages is controlled to be 60% of the unit mass mechanical energy input in the front stage. The unit mass mechanical energy input is calculated by the operating power, no-load power and material mass flow rate of the twin-screw extruder. That is, the operating power of the twin-screw extruder is subtracted from the no-load power to obtain the effective power consumed by the material mixing. Then, the effective power is divided by the mass of material passing through the twin-screw extruder per unit time to obtain the unit mass mechanical energy input.
[0068] After low-damage mixing in the middle and later stages, the thermal history-responsive latent degradation particles are dispersed in the continuous polyester melt, and the solid phase boundary layer remains unbroken. The shell penetration damage rate of the thermal history-responsive latent degradation particles after melt mixing is 3.2%.
[0069] In S5, after degassing, extrusion, cooling, and pelletizing, engineered granules of polyester biodegradable plastic are obtained.
[0070] Specifically, the melt after low-damage mixing in the middle and later stages is transported to the exhaust zone, where low-molecular-weight volatiles and residual moisture are removed under negative pressure exhaust conditions.
[0071] After the venting is completed, the melt is extruded through the die head to form strips. The strips are then cooled in a water cooling tank with the cooling water temperature controlled at 20°C to 25°C. The cooled strips are then pelletized by a pelletizer to obtain the initial product of polyester biodegradable plastic engineering pellets.
[0072] S5 is followed by a dehumidification and crystallization step, which involves treating the granulated engineered particles at 45°C to 85°C for 0.5 to 6 hours to achieve a moisture content of 100 ppm to 800 ppm.
[0073] Specifically, the initial engineered granules were placed in a dehumidifying crystallization device and treated at 65°C for 3 hours. After dehumidifying crystallization and shaping, an engineered granule of polyester biodegradable plastic was obtained. In the obtained engineered granules, the engineered supporting component and the thermally history-responsive latent degradable particles were both dispersed in the continuous phase formed by the polyester biodegradable resin. According to cross-sectional microscopic images, the direct contact area ratio between the engineered supporting component and the thermally history-responsive latent degradable particles was 8.6%, and the water content of the engineered granules was 430 ppm.
[0074] After solid-phase crushing treatment, the exposed proportion of hydrophilic and biodegradable core material on the crushed section of the products obtained by the above-mentioned engineering particles through secondary melting and molding is 20% to 60%.
[0075] Specifically, after the obtained engineering particles are subjected to secondary melting and solid-phase crushing treatment, the exposure ratio of the hydrophilic and biodegradable core material on the fracture surface is 43.5%.
[0076] Material sources and preparation methods:
[0077] The polylactic acid used in this invention was purchased from Zhejiang Hisun Biomaterials Co., Ltd., model REVODE190, and was dehumidified and dried at 55°C for 6 hours before use.
[0078] The polybutylene adipate terephthalate used in this invention was purchased from Xinjiang Lanshan Tunhe Technology Co., Ltd., model TH801T-MF, and was dehumidified and dried at 55°C for 6 hours before use.
[0079] The polybutylene succinate used in this invention was purchased from Xinjiang Lanshan Tunhe Technology Co., Ltd., model TH803S, and was dehumidified and dried at 55°C for 6 hours before use.
[0080] The talc powder used in this invention was purchased from Guangxi Longsheng Huamei Talc Development Co., Ltd., and is a 3000-mesh fine talc powder with an average particle size of 3.0μm to 3.5μm.
[0081] The silane coupling agent used in this invention was purchased from Nanjing Shuguang Fine Chemical Co., Ltd., model number SG-Si1100, common name KH-550.
[0082] The corn starch used in this invention was purchased from COFCO Biotechnology Co., Ltd., in 25kg bags, and was vacuum dried at 60°C for 6 hours before use.
[0083] The microcrystalline cellulose used in this invention was purchased from Qufu Tianli Pharmaceutical Excipients Co., Ltd., model PH101, and was vacuum dried at 60°C for 6 hours before use.
[0084] The maleic anhydride-grafted polyester used in this invention was purchased from KOAS Chemical Co., Ltd., and its model number is BP-1.
[0085] The epoxy functionalized compatibilizer used in this invention was purchased from KOAS Chemical Co., Ltd., and its model number is W5A.
[0086] The multifunctional epoxy chain extender used in this invention was purchased from Jia Yi Rong Polymers (Shanghai) Co., Ltd., and its model is Fine-Blend SAG-008.
[0087] The flexible aliphatic polyester layer material used in this invention was purchased from Shenzhen Guanghua Weiye Co., Ltd., and the model is polycaprolactone PCL 600C.
[0088] The ethyl acetate used in this invention is an analytical grade reagent with a purity of 99.5% and a water content of no more than 0.05%.
[0089] The acetone used in this invention is an analytical grade reagent with a purity of 99.5% and a water content of no more than 0.05%.
[0090] The anhydrous ethanol used in this invention is an analytical grade reagent with a volume fraction of 99.7%.
[0091] The glacial acetic acid used in this invention is an analytical grade reagent with a mass fraction of not less than 99.5%.
[0092] The liquid nitrogen used in this invention is industrial-grade liquid nitrogen with a purity of not less than 99.9%.
[0093] The talc powder treated with silane coupling was prepared as follows: Talc powder (3000 mesh, purchased from Guangxi Longsheng Huamei Talc Development Co., Ltd.) was placed in a forced-air drying oven and dried at 105℃ for 4 hours. After cooling to 25℃, it was ready for use. Anhydrous ethanol and deionized water were mixed at a volume ratio of 95:5. Glacial acetic acid was added to adjust the pH to 4.5. Then, silane coupling agent KH-550 (SG-Si 1100, purchased from Nanjing Shuguang Fine Chemical Co., Ltd.) was added to prepare a coupling treatment solution with a silane mass fraction of 1.5%. The dried talc powder was added to a high-speed mixer at a speed of 900 r / min. The coupling treatment solution was sprayed into the talc powder at a ratio of 1.0% of the silane coupling agent by mass for 6 minutes. After spraying, mixing continued for 20 minutes. The mixed talc powder was placed in a forced-air drying oven and dried at 110℃ for 2 hours. Then, it was classified by an air classifier, and the powder with an average particle size of 3.2μm was collected to obtain talc powder treated with silane coupling.
[0094] The brittle polyester microlayer material was prepared as follows: 100 parts of polylactic acid (PLA) of model REVODE190 (purchased from Zhejiang Hisun Biomaterials Co., Ltd.), 12 parts of talc powder (3000 mesh micro-fine talc powder) of model 12000 (purchased from Guangxi Longsheng Huamei Talc Development Co., Ltd.), and 3 parts of maleic anhydride grafted polyester (Mr. BP-1) of model 12000 (purchased from Keasi Chemical Co., Ltd.) were added to a mixer. The mixing temperature was controlled at 155℃, the rotor speed at 60 r / min, and the mixing time at 8 min, so that the talc powder was dispersed in the continuous phase of PLA. After the mixer was removed, it was cold-pressed into sheets at a temperature of 25℃, a pressure of 5 MPa, and a time of 2 min. The cold-pressed sheets were cooled under liquid nitrogen for 5 min, and then pulverized by a cryogenic pulverizer at a speed of 12000 r / min for 3 min. The pulverized powder was subjected to airflow classification to collect polylactic acid-based brittle composite powder with a D50 of 6.0 μm, yielding a crackable polyester microlayer material. The Vicat softening temperature of the above-mentioned crackable polyester microlayer material is 85℃.
[0095] The hydrophilic biodegradable core material was prepared as follows: Corn starch (25kg bags, purchased from COFCO Biotechnology Co., Ltd.) was placed in a vacuum drying oven and dried at 60℃ for 6 hours. Microcrystalline cellulose (PH101, purchased from Qufu Tianli Pharmaceutical Excipients Co., Ltd.) was placed in a vacuum drying oven and dried at 60℃ for 6 hours. 70 parts of the dried corn starch and 30 parts of the dried microcrystalline cellulose were added to a high-speed mixer, and the mixing speed was controlled at 800 r / min for 8 minutes to obtain a hydrophilic biodegradable core material premix powder. The above hydrophilic biodegradable core material premix powder was graded using an airflow sieving device, with the grading wheel speed controlled at 2800 r / min and the feed rate at 300 g / min. Core material particles with an average particle size of 35 μm were collected to obtain the hydrophilic biodegradable core material.
[0096] Thermally responsive latent degradable particles were prepared as follows: The aforementioned brittle polyester microlayer material was added to a mixed solvent of ethyl acetate and acetone at a mass ratio of 6:4. The mixture was stirred at 25°C for 40 min at a stirring speed of 500 r / min to obtain a solid-phase boundary-breaking coating solution with a mass fraction of 8%. The aforementioned hydrophilic biodegradable core material was added to the material chamber of a fluidized bed bottom spray coating device. The inlet air temperature was controlled at 40°C, the outlet air temperature at 32°C, the atomization pressure at 0.20 MPa, and the bottom spraying speed at 5 g / min. The solid-phase boundary-breaking coating solution was sprayed into the bottom of the fluidized bed, causing the brittle polyester microlayer material to evaporate with the solvent and deposit on the outside of the hydrophilic biodegradable core material. After the solid-phase boundary-breaking coating solution was sprayed in, the particles were further fluidized and dried at 40°C for 30 min. The particles were then placed in a 45°C vacuum drying oven for 3 h, and agglomerated particles were removed by a vibrating screen to obtain intermediate particles with a solid-phase boundary-breaking layer. The thickness of the resulting solid-phase boundary layer was 1.6 μm.
[0097] Flexible aliphatic polyester layer material, model polycaprolactone PCL 600C, purchased from Shenzhen Guanghua Weiye Co., Ltd., was placed in a jacketed melting tank. The temperature of the melting tank was controlled at 100℃ to soften the flexible aliphatic polyester layer material into a semi-molten state. Intermediate particles with a solid-phase breaking layer were added to a roller-type melting and coating equipment. The jacket temperature was controlled at 100℃ and the roller speed was 30 r / min. The semi-molten flexible aliphatic polyester layer material was added to the roller-type melting and coating equipment in 5 batches, with each addition followed by 4 minutes of rolling. After all the material was added, rolling continued for 20 minutes.
[0098] After rolling, dry air at 28°C is introduced into the drum-type melt rolling equipment to cool and solidify the melt shear buffer layer on the particle surface. The cooled particles are then removed and depolymerized at a low speed of 80 r / min for 3 min. Particles with an average particle size of 58 μm are then collected by sieving, yielding thermally responsive latent degradation particles. The resulting melt shear buffer layer has a thickness of 3.2 μm, a softening temperature of 65°C, and a softening temperature of 85°C for the solid-phase breaking layer. The softening temperature of the melt shear buffer layer is 20°C lower than that of the solid-phase breaking layer.
[0099] Ordinary dense polyester monolayer coated hydrophilic particles are prepared as follows: Polylactic acid (PLA) of model REVODE190, purchased from Zhejiang Hisun Biomaterials Co., Ltd., is added to a mixed solvent of ethyl acetate and acetone, with a mass ratio of 6:4. The mixture is stirred at 25°C for 40 min at a stirring speed of 500 r / min to obtain a PLA coating solution with a mass fraction of 8%.
[0100] The aforementioned hydrophilic biodegradable core material was added to the material chamber of a fluidized bed bottom spray coating device. The inlet air temperature was controlled at 40℃, the outlet air temperature at 32℃, the atomization pressure at 0.20MPa, and the bottom spraying speed at 5g / min. Polylactic acid coating solution was sprayed into the bottom of the fluidized bed, allowing the polylactic acid to evaporate with the solvent and deposit on the outer side of the hydrophilic biodegradable core material. After spraying, the material was further fluidized and dried under 40℃ hot air for 30 minutes, and then placed in a 45℃ vacuum drying oven for 3 hours. After sieving, particles with an average particle size of 58μm were collected to obtain ordinary dense polyester single-layer coated hydrophilic particles.
[0101] Experimental methods:
[0102] Before testing, the polyester biodegradable plastic engineering granules prepared in the examples and comparative examples were added to an injection molding machine for secondary melt molding. The barrel temperature of the injection molding machine was controlled at 175°C to 185°C, the mold temperature at 30°C, and the injection pressure at 70MPa to prepare standard specimens for mechanical property testing. The standard specimens were then conditioned in a standard environment at 23°C and 50% relative humidity for 48 hours before testing. The specimen conditioning and test environment were carried out in accordance with GB / T 2918-2018 "Standard Environment for Conditioning and Testing of Plastic Specimens", which is currently the existing standard.
[0103] Tensile strength was tested according to GB / T 1040.2-2022 "Determination of tensile properties of plastics - Part 2: Test conditions for molded and extruded plastics". During the test, the standard specimen after condition conditioning was installed in the fixture of the electronic universal testing machine and stretched at a specified speed. The maximum load borne by the specimen during the stretching process was recorded, and the tensile strength was calculated according to the ratio of the maximum load to the original cross-sectional area of the specimen. That is, the tensile strength is equal to the maximum tensile load divided by the original cross-sectional area of the gauge length of the specimen, and the unit is MPa. No less than 5 specimens were tested for each group of samples, and the average value was taken as the tensile strength of the group of samples.
[0104] The flexural modulus was tested according to GB / T 9341-2008 "Determination of Flexural Properties of Plastics". During the test, the standard specimen after condition adjustment was placed on a three-point bending fixture, so that the two ends of the specimen were supported and loaded in the middle of the span. The relationship between load and deflection during the loading process was recorded. The ratio of bending stress to bending strain was calculated within the linear range of the load-deflection curve to obtain the flexural modulus, which is in MPa. At least 5 specimens were tested for each group of samples, and the average value was taken as the flexural modulus of the group of samples.
[0105] Notched impact strength was tested according to GB / T 1843-2008 "Determination of Impact Strength of Plastic Cantilever Beams". Before the test, a notch of a specified size was prepared in the middle of the standard specimen. After the notched specimen was conditioned in a standard environment, the cantilever beam impact test was carried out. The impact energy absorbed when the specimen was broken was recorded. The notched impact strength was calculated as the ratio of the impact absorbed energy to the remaining cross-sectional area at the notch, with the unit being kJ / m². At least 5 specimens were tested for each group of samples, and the average value was taken as the notched impact strength of the group of samples.
[0106] The MFR change rate was tested according to GB / T 3682.1-2018 "Determination of melt mass flow rate and melt volume flow rate of thermoplastic plastics - Part 1: Standard method". During the test, the melt mass flow rate MFR1 before secondary melt molding and the melt mass flow rate MFR2 after secondary melt molding of the engineering particles were measured. The test temperature and load were kept consistent in each example and comparative example. The MFR was obtained by converting the extruded mass within the specified time to the extruded mass in 10 min, and the unit is g / 10 min. The MFR change rate was calculated by dividing the absolute value of the difference between MFR2 and MFR1 by MFR1 and then multiplying by 100%, and was used to evaluate the melt flow stability of the engineering particles after secondary melt molding.
[0107] The shell penetration failure rate was determined using scanning electron microscopy and image statistical methods. During testing, engineering particles or secondary melt-formed samples were taken after melt-mixing, subjected to low-temperature brittle fracture or slicing, and then sputter-coated with gold for observation. At least five fields of view were randomly selected, and the total number of thermally history-responsive latent degradation particles within each field of view, as well as the number of particles exhibiting penetrating cracks, penetrating pores, or premature exposure of the hydrophilic biodegradable core material, were counted. The shell penetration failure rate was calculated by dividing the number of particles with penetrating failure by the total number of observed particles and multiplying by 100%. This index characterizes the shell integrity of thermally history-responsive latent degradation particles during melt granulation and secondary melt-forming processes.
[0108] The core material exposure ratio was determined using solid-phase fracture microscopic observation and image area statistics. During testing, the sample, after secondary melting and molding, underwent solid-phase fracture treatment. Fractured sections were observed using scanning electron microscopy or optical microscopy. At least five cross-sectional fields were randomly selected to identify the thermally history-responsive latent degradation particle regions and the exposed hydrophilic degradable core material areas within them. The core material exposure ratio was calculated by dividing the exposed area of the hydrophilic degradable core material by the total area of the thermally history-responsive latent degradation particle cross-section, and then multiplying by 100%. This index is used to evaluate the ability of the solid-phase fracture layer to form a fracture opening and expose the hydrophilic degradable core material during the waste fracture stage.
[0109] The direct contact area ratio was determined using a statistical method based on microscopic images of the engineered particle cross-section. During testing, engineered particles or secondary melt-molded samples were taken, and their cross-sectional morphology was observed after low-temperature brittle fracture, slicing, or polishing. At least five cross-sectional fields were randomly selected to identify the direct contact areas between the engineered support component and the thermally history-responsive latently degradable particles that were not separated by a continuous polyester layer. The outer surface area of the thermally history-responsive latently degradable particles was also identified. The direct contact area ratio was calculated by dividing the direct contact area between the engineered support component and the thermally history-responsive latently degradable particles by the outer surface area of the thermally history-responsive latently degradable particles, and then multiplying by 100%. This index is used to evaluate the degree of interfacial isolation between the engineered support component and the thermally history-responsive latently degradable particles.
[0110] Moisture content was determined according to GB / T 6283-2008 "Determination of Moisture Content in Chemical Products - Karl Fischer Method". During the test, dehumidified, crystallized, and shaped engineering granules were used as samples. The samples were sheared or crushed into small particles suitable for testing before Karl Fischer moisture determination. The moisture content was calculated as the ratio of the measured moisture mass to the sample mass and expressed in ppm. That is, the moisture content equals the sample moisture mass divided by the sample mass multiplied by 10. 6 .
[0111] The 45-day phased biodegradation rate was determined according to GB / T 19277.1-2025 "Determination of the final aerobic biodegradability of materials under controlled composting conditions - Method for determining the release of carbon dioxide - Part 1: General method". During the test, the sample, which had undergone secondary melting and solid-phase crushing, was placed in a controlled composting system. The composting biodegradation test was carried out under specified temperature, humidity and aeration conditions. The amount of carbon dioxide released by the test system within 45 days was measured continuously or periodically. A blank control system was set up at the same time. The 45-day phased biodegradation rate was calculated by multiplying the ratio of the cumulative carbon dioxide release of the test sample over 45 days minus the cumulative carbon dioxide release of the blank control over 45 days to the theoretical carbon dioxide release of the sample by 100%. The above 45-day phased biodegradation rate is used to evaluate the effect of the water entry path formed by the exposure of hydrophilic degradable core material after the engineering particles are crushed by waste solid phase on the early biodegradation initiation ability.
[0112] Example 1:
[0113] This embodiment provides engineering particles of polyester biodegradable plastic. By weight, 100 parts of polyester biodegradable resin, 20 parts of engineering support component, 14 parts of thermal history-responsive latent degradable particles, 3 parts of compatibility control component, and 0.8 parts of chain extension control component are prepared. The polyester biodegradable resin is composed of 60 parts of polylactic acid, 30 parts of polybutylene adipate terephthalate, and 10 parts of polybutylene succinate. The engineering support component is talc powder treated with silane coupling, with an average particle size of 3.2 μm. The compatibility control component is a mixture of maleic anhydride-grafted polyester and epoxy functionalized compatibilizer in a mass ratio of 2:1. The chain extension control component is a multifunctional epoxy chain extender.
[0114] The aforementioned thermally responsive latent degradable particles include a hydrophilic degradable core material, a solid-phase boundary-breaking layer coating the outside of the hydrophilic degradable core material, and a melt shear buffer layer coating the outside of the solid-phase boundary-breaking layer. The hydrophilic degradable core material is composed of corn starch and microcrystalline cellulose in a mass ratio of 7:3. The solid-phase boundary-breaking layer is made of a brittle polyester microlayer, and the melt shear buffer layer is made of a flexible aliphatic polyester layer. The thickness of the solid-phase boundary-breaking layer is 1.6 μm, and the thickness of the melt shear buffer layer is 3.2 μm. The softening temperature of the melt shear buffer layer is 20°C lower than that of the solid-phase boundary-breaking layer.
[0115] To prepare thermally history-responsive latent degradable particles, corn starch and microcrystalline cellulose were first placed in a vacuum drying oven and dried at 60°C for 6 hours to ensure that the moisture content of both corn starch and microcrystalline cellulose was below 800 ppm. Then, the dried corn starch and microcrystalline cellulose were added to a high-speed mixer at a mass ratio of 7:3 and mixed at 800 r / min for 8 minutes to form a uniformly dispersed hydrophilic degradable core material premix powder. The hydrophilic degradable core material premix powder was then graded using an airflow sieving device to remove oversized agglomerated particles and undersized fine powder, and core material particles with an average particle size of 35 μm were collected as hydrophilic degradable core material for subsequent coating.
[0116] The brittle polyester microlayer material was added to a mixed solvent of ethyl acetate and acetone and stirred at room temperature for 40 minutes to fully dissolve or uniformly disperse the brittle polyester microlayer material, resulting in a solid-phase boundary-breaking coating liquid with a mass fraction of 8%. The above hydrophilic biodegradable core material was added to the material chamber of the fluidized bed bottom spray coating equipment, and the air inlet system was turned on to keep the hydrophilic biodegradable core material in a stable fluidized state under the action of airflow. The air inlet temperature of the fluidized bed bottom spray coating equipment was controlled at 38°C to 42°C, the air outlet temperature at 30°C to 35°C, and the atomization pressure at 0.18MPa to 0.22MPa. After the hydrophilic biodegradable core material was kept in a stable fluidized state, the solid-phase boundary-breaking coating liquid was sprayed into the bottom of the fluidized bed through the bottom spray gun, and the spraying speed was controlled at 4g / min to 6g / min, so that the solid-phase boundary-breaking coating liquid entered the spaces between the fluidized core material particles in a fine mist state.
[0117] During the spray coating process, droplets in the solid-phase boundary-breaking coating liquid adhere to the surface of the hydrophilic biodegradable core material. The mixed solvent gradually evaporates under the action of hot air, and the brittle polyester microlayer material is deposited layer by layer with the solvent evaporation and coats the outside of the hydrophilic biodegradable core material. At the same time, the core material particles are continuously turned and dispersed, so that the solid-phase boundary-breaking material forms a relatively uniform coating layer on the outer surface of the hydrophilic biodegradable core material, avoiding the formation of local agglomerates or large areas of bareness. After the solid-phase boundary-breaking coating liquid is sprayed in, hot air fluidization drying is maintained at 38°C to 42°C for 30 minutes to further evaporate the residual solvent in the coating layer and to preliminarily shape the solid-phase boundary-breaking layer. Then, the preliminarily coated particles are taken out and placed in a vacuum drying oven at 45°C for 3 hours to reduce the residual solvent content and improve the continuity of the solid-phase boundary-breaking layer. Then, the particles are sieved through a vibrating screen to remove obviously agglomerated particles and fine powder that has not been effectively coated, resulting in intermediate particles with a solid-phase boundary-breaking layer.
[0118] Flexible aliphatic polyester layer material is used as the melt shear buffer layer material. The flexible aliphatic polyester layer material is pre-placed in a jacketed molten material tank. The temperature of the molten material tank is controlled at 95℃ to 105℃ to soften the flexible aliphatic polyester layer material into an adhesive semi-molten state. Then, the intermediate particles with the solid phase breaking layer are added to the drum-type melt rolling equipment. The jacket temperature of the drum-type melt rolling equipment is controlled at 95℃ to 105℃ and the drum speed is 25r / min to 35r / min. Under the continuous tumbling state of the intermediate particles, the softened flexible aliphatic polyester layer material is added to the drum-type melt rolling equipment in small amounts and multiple times, so that the flexible aliphatic polyester layer material repeatedly contacts, spreads and adheres to the outside of the solid phase breaking layer between the particles.
[0119] After each addition of the flexible aliphatic polyester layer material, continue rolling for 3 to 5 minutes before adding the next material to avoid excessive addition that could cause the particles to clump together. After all the flexible aliphatic polyester layer material has been added, continue rolling for 20 minutes to further homogenize the melt shear buffer layer outside the solid phase breaking layer. After rolling, dry air at a temperature of 25°C to 30°C is introduced into the drum-type melt rolling equipment to gradually cool and solidify the melt shear buffer layer on the particle surface. The cooled particles are then removed and subjected to mild depolymerization using a low-speed paddle mixing method at a speed of 80 r / min for 3 minutes to break up the slightly agglomerated particles while avoiding damage to the particle shell structure. The depolymerized particles are then sieved, and particles with an average particle size of 58 μm are collected to obtain thermally responsive latent degradation particles.
[0120] Scanning electron microscopy was used to observe the cross-section of the thermally responsive latent degradation particles. It was confirmed that the hydrophilic biodegradable core material was located inside, the solid-phase boundary layer was wrapped around the outside of the hydrophilic biodegradable core material, and the melt shear buffer layer was wrapped around the outside of the solid-phase boundary layer. Neither the solid-phase boundary layer nor the melt shear buffer layer showed any through-cracks.
[0121] In preparing polyester biodegradable plastic engineering particles, polylactic acid, polybutylene adipate terephthalate, and polybutylene succinate are placed in a dehumidifying dryer and dried at 55°C for 6 hours. Talc powder treated with silane coupling is placed in an 80°C forced-air drying oven and dried for 4 hours. Then, the dried polylactic acid, polybutylene adipate terephthalate, polybutylene succinate, silane-coupled talc powder, compatibility control components, and chain expansion control components are added to a high-speed mixer. The speed of the high-speed mixer is controlled at 600 r / min, and the mixture is mixed for 10 minutes to pre-disperse the engineering support components, compatibility control components, and chain expansion control components between the polyester biodegradable resin particles, thus obtaining a premix for front-end melt composite.
[0122] The premixed material for the front-end melt compounding process is added to the main feed port of a twin-screw extruder. The twin-screw extruder is sequentially configured with a front-end melt compounding zone, a mid-to-rear low-damage mixing zone, a venting zone, and an extrusion granulation zone along the material conveying direction. The barrel temperature of the front-end melt compounding zone is controlled at 170℃, 175℃, 180℃, and 185℃ respectively, and the screw speed is controlled at 280 r / min. This allows the biodegradable polyester resin to gradually melt and form a continuous melt. The engineering support component is dispersed in the continuous polyester melt under the action of the compatibility control component. At the same time, the chain expansion control component regulates the processing stability of the polyester melt, thereby obtaining a continuous polyester melt containing the engineering support component.
[0123] After a stable continuous polyester melt is formed in the front section of the molten composite zone, the aforementioned thermally responsive latent degradation particles are added through the side feed port located in the middle and rear section of the twin-screw extruder. The barrel temperature before and after the side feed port is controlled at 168°C to 176°C. The unit mass mechanical energy input in the middle and rear low-damage mixing zone is controlled to be 60% of the unit mass mechanical energy input in the front section. The unit mass mechanical energy input is calculated by the operating power, no-load power, and material mass flow rate of the twin-screw extruder. That is, the operating power of the twin-screw extruder is subtracted from the no-load power to obtain the effective power consumed in material mixing. Then, the effective power is divided by the mass of material passing through the twin-screw extruder per unit time to obtain the unit mass mechanical energy input.
[0124] In the mid-to-late stage low-damage mixing zone, thermally responsive latent degradable particles are dispersed in a continuous polyester melt containing engineering support components. Because the thermally responsive latent degradable particles are provided with a melt shear buffer layer on the outside, they can buffer the screw shear and particle collision during the mid-to-late stage low-damage mixing process, keeping the solid phase boundary layer from breaking through and preventing the hydrophilic degradable core material from being exposed prematurely during the melt granulation stage and causing hydrolysis of the continuous polyester phase.
[0125] The melt, after undergoing low-damage mixing in the middle and later stages, is transported to the exhaust zone. Under negative pressure exhaust conditions, low-molecular-weight volatiles and residual moisture in the melt are removed. The exhaust melt is then extruded through the die head to form strips. The strips are then cooled through a water cooling tank, with the cooling water temperature controlled at 20°C to 25°C. Subsequently, the cooled strips are pelletized by a pelletizer to obtain the initial product of polyester biodegradable plastic engineering granules.
[0126] The above-mentioned preliminary engineering particles were placed in a dehumidifying crystallization device and treated at 65°C for 3 hours. After dehumidifying crystallization and shaping, a polyester biodegradable plastic engineering particle was obtained. In the obtained engineering particles, the engineering support component and the thermal history-responsive latent degradable particles were dispersed in the continuous phase formed by the polyester biodegradable resin. The thermal history-responsive latent degradable particles include a hydrophilic biodegradable core material, a solid phase breaking layer and a melt shear buffer layer. According to the cross-sectional microscopic images, the direct contact area ratio between the engineering support component and the thermal history-responsive latent degradable particles was 8.6%, and the water content of the engineering particles was 430 ppm.
[0127] When the above-mentioned polyester biodegradable plastic engineering granules are used for performance testing, the engineering granules are added to an injection molding machine for secondary melt molding. The temperature of the injection molding machine barrel is controlled at 175℃ to 185℃, the mold temperature is 30℃, and the injection pressure is 70MPa. After injection molding, standard specimens are obtained. The above standard specimens are conditioned at 23℃ and 50% relative humidity for 48 hours before performance testing.
[0128] Example 2:
[0129] The difference between this embodiment and Embodiment 1 is that the amount of thermal history-responsive latent degradation particles is 3 parts. Apart from the above differences, the other raw material types, preparation methods of thermal history-responsive latent degradation particles, extrusion granulation methods of engineered particles, side feeding methods, and dehumidification crystallization and shaping conditions are the same as in Embodiment 1.
[0130] Example 3:
[0131] The difference between this embodiment and Embodiment 1 is that the amount of thermal history-responsive latent degradation particles used is 25 parts. Apart from the above differences, the other raw material types, preparation methods of thermal history-responsive latent degradation particles, extrusion granulation methods of engineered particles, side feeding methods, and dehumidification crystallization and shaping conditions are the same as in Embodiment 1.
[0132] Example 4:
[0133] The difference between this embodiment and Embodiment 1 is that the amount of the engineering support component is 5 parts. Apart from the above differences, the other raw material types, the preparation method of thermal history-responsive latent degradation particles, the extrusion granulation method of engineering particles, the side feeding method, and the dehumidification crystallization and shaping conditions are the same as those in Embodiment 1.
[0134] Example 5:
[0135] The difference between this embodiment and Embodiment 1 is that the amount of the engineering support component is 35 parts. Apart from the above differences, the other raw material types, the preparation method of thermal history-responsive latent degradation particles, the extrusion granulation method of engineering particles, the side feeding method, and the dehumidification crystallization and shaping conditions are the same as those in Embodiment 1.
[0136] Example 6:
[0137] The difference between this embodiment and Example 1 is that the thickness of the solid-phase boundary-breaking layer is 0.2 μm. When preparing thermal history-responsive latent degradation particles, the total amount of solid-phase boundary-breaking coating liquid injected is reduced, and the spray coating time is shortened to about 13% of that in Example 1. Apart from the above differences, the other raw material types, preparation methods of thermal history-responsive latent degradation particles, extrusion granulation methods of engineering particles, side feeding methods, and dehumidification crystallization and shaping conditions are the same as in Example 1.
[0138] Example 7:
[0139] The difference between this embodiment and Embodiment 1 is that the thickness of the solid-phase boundary-breaking layer is 5.0 μm. When preparing thermal history-responsive latent degradation particles, the total amount of solid-phase boundary-breaking coating liquid injected is increased and the spray coating time is extended. Apart from the above differences, the other raw material types, preparation methods of thermal history-responsive latent degradation particles, extrusion granulation methods of engineering particles, side feeding methods, and dehumidification crystallization and shaping conditions are the same as in Embodiment 1.
[0140] Example 8:
[0141] The difference between this embodiment and Embodiment 1 is that the melt shear buffer layer thickness is 0.5 μm. When preparing thermally responsive latent degradation particles, the amount of flexible aliphatic polyester layer material added is reduced, and the melt rolling time is shortened. Apart from the above differences, the other raw material types, thermally responsive latent degradation particle preparation methods, engineering particle extrusion granulation methods, side feeding methods, and dehumidification crystallization and shaping conditions are the same as in Embodiment 1.
[0142] Example 9:
[0143] The difference between this embodiment and Embodiment 1 is that the melt shear buffer layer thickness is 8.0 μm. When preparing thermally responsive latent degradation particles, the amount of flexible aliphatic polyester layer material added is increased, and the melt rolling time is extended. Apart from the above differences, the other raw material types, thermally responsive latent degradation particle preparation methods, engineering particle extrusion granulation methods, side feeding methods, and dehumidification crystallization and shaping conditions are the same as in Embodiment 1.
[0144] Example 10:
[0145] The difference between this embodiment and Embodiment 1 is that the mechanical energy input per unit mass in the low-damage mixing zone in the middle and later stages is 35% of that in the front stage. Apart from the above differences, the other raw material types, the preparation method of thermal history-responsive latent degradation particles, the extrusion granulation method of engineering particles, the side feeding method, and the dehumidification crystallization and shaping conditions are all the same as in Embodiment 1.
[0146] Example 11:
[0147] The difference between this embodiment and Embodiment 1 is that the mechanical energy input per unit mass in the low-damage mixing zone in the middle and later stages is 85% of that in the front stage. Apart from the above differences, the other raw material types, the preparation method of thermal history-responsive latent degradation particles, the extrusion granulation method of engineering particles, the side feeding method, and the dehumidification crystallization and shaping conditions are all the same as in Embodiment 1.
[0148] Comparative Example 1:
[0149] The difference between this comparative example and Example 1 is that, instead of preparing thermally responsive latent degradable particles, corn starch and microcrystalline cellulose are directly added to polyester biodegradable resin in the proportion of hydrophilic biodegradable core material in Example 1 for blending. Apart from the above differences, the dosage of other components, extrusion temperature, screw speed, cooling pelleting and dehumidification crystallization conditions are the same as in Example 1.
[0150] Comparative Example 2:
[0151] The difference between this comparative example and Example 1 is that the thermal history-responsive latent degradation particles are replaced with ordinary dense polyester monolayer coated hydrophilic particles. The above-mentioned ordinary dense polyester monolayer coated hydrophilic particles do not have a solid-phase breaking layer and a melt shear buffer layer, nor are they limited to the softening temperature difference between the coating layer and the solid-phase breaking layer. Apart from the above differences, the dosage of other components, extrusion temperature, screw speed, cooling pelletizing and dehumidification crystallization conditions are the same as those in Example 1.
[0152] Comparative Example 3:
[0153] The difference between this comparative example and Example 1 is that the thermally responsive latent degradation particles do not have a melt shear buffer layer, but only include a hydrophilic biodegradable core material and a solid-phase breaking layer. Apart from the above differences, the dosage of other components, extrusion temperature, screw speed, cooling pelletizing and dehumidification crystallization conditions are the same as those in Example 1.
[0154] Comparative Example 4:
[0155] The difference between this comparative example and Example 1 is that the thermally responsive latent degradation particles do not have a solid-phase breaking layer, but only retain a hydrophilic biodegradable core material and a melt shear buffer layer with a thickness of 3.2 μm. Apart from the above differences, the dosage of other components, the melt shear buffer layer material, the extrusion temperature, the screw speed, the cooling pelletizing and dehumidification crystallization conditions are the same as those in Example 1.
[0156] Comparative Example 5:
[0157] The difference between this comparative example and Example 1 is that the amount of thermally responsive latent degradation particles is 2.5 parts. Apart from the above differences, the amounts of other components, extrusion temperature, screw speed, cooling pelletizing and dehumidification crystallization conditions are the same as in Example 1.
[0158] Comparative Example 6:
[0159] The difference between this comparative example and Example 1 is that the amount of thermally responsive latent degradation particles is 26.5 parts. Apart from the above differences, the amounts of other components, extrusion temperature, screw speed, cooling pelletizing and dehumidification crystallization conditions are the same as in Example 1.
[0160] Comparative Example 7:
[0161] The difference between this comparative example and Example 1 is that the amount of engineering support component is 4.5 parts. Apart from the above differences, the amounts of other components, extrusion temperature, screw speed, cooling pelletizing and dehumidification crystallization conditions are the same as those in Example 1.
[0162] Comparative Example 8:
[0163] The difference between this comparative example and Example 1 is that the amount of engineering support component is 37 parts. Apart from the above differences, the amounts of other components, extrusion temperature, screw speed, cooling pelletizing and dehumidification crystallization conditions are the same as those in Example 1.
[0164] Comparative Example 9:
[0165] The difference between this comparative example and Example 1 is that the thickness of the solid-phase breaking layer is 0.15 μm. Apart from the above differences, the amounts of other components, extrusion temperature, screw speed, cooling pelletizing and dehumidification crystallization conditions are the same as those in Example 1.
[0166] Comparative Example 10:
[0167] The difference between this comparative example and Example 1 is that the thickness of the solid-phase boundary layer is 5.3 μm. Apart from the above differences, the amounts of other components, extrusion temperature, screw speed, cooling pelletizing and dehumidification crystallization conditions are the same as those in Example 1.
[0168] Comparative Example 11:
[0169] The difference between this comparative example and Example 1 is that the melt shear buffer layer thickness is 0.4 μm. Apart from the above differences, the amounts of other components, extrusion temperature, screw speed, cooling pelletizing and dehumidification crystallization conditions are the same as those in Example 1.
[0170] Comparative Example 12:
[0171] The difference between this comparative example and Example 1 is that the melt shear buffer layer thickness is 8.4 μm. Apart from the above differences, the amounts of other components, extrusion temperature, screw speed, cooling pelletizing and dehumidification crystallization conditions are the same as those in Example 1.
[0172] Comparative Example 13:
[0173] The difference between this comparative example and Example 1 is that the mechanical energy input per unit mass in the low-damage mixing zone in the middle and later stages is 32% of that in the front stage. Apart from the above differences, the dosage of other components, extrusion temperature, screw speed, cooling pelletizing and dehumidification crystallization conditions are the same as in Example 1.
[0174] Comparative Example 14:
[0175] The difference between this comparative example and Example 1 is that the mechanical energy input per unit mass in the low-damage mixing zone in the middle and later stages is 88% of that in the front stage. Apart from the above differences, the dosage of other components, extrusion temperature, screw speed, cooling pelletizing and dehumidification crystallization conditions are the same as in Example 1.
[0176] Comparative Example 15:
[0177] The difference between this comparative example and Example 1 is that the thermal history-responsive latent degradation particles and the engineering support component are added simultaneously through the same main feed port, so that the engineering support component and the thermal history-responsive latent degradation particles first undergo local contact and agglomeration before entering the polyester continuous melt. According to cross-sectional microscopic images, the direct contact area ratio between the engineering support component and the thermal history-responsive latent degradation particles in this comparative example is 27.8%. Apart from the above differences, the dosage of other components, extrusion temperature, screw speed, cooling pelletizing and dehumidification crystallization conditions are the same as those in Example 1.
[0178] The experimental data are shown in the table below:
[0179] Table 1. Parameters of Examples and Comparative Examples
[0180] Group Tensile strength (MPa) Flexural modulus (MPa) Notched impact strength kJ / m² MFR change rate % Shell penetration failure rate % Core material exposure ratio % Direct contact area percentage Moisture content (ppm) 45-day stage biodegradation rate % Example 1 47.8 2486 8.4 7.1 3.2 43.5 8.6 430 48.6 Example 2 51.2 2561 8.9 4.8 2.4 24.7 6.2 386 31.5 Example 3 42.6 2268 6.7 8.6 6.6 55.8 13.7 512 61.3 Example 4 43.4 1845 9.1 6.5 3.1 42.1 5.4 421 47.9 Example 5 50.5 3192 5.8 9.4 5.7 38.6 16.1 475 42.7 Example 6 45.7 2414 7.6 9.8 7.3 57.2 9.5 468 58.9 Example 7 49.6 2528 8.2 5.2 1.8 23.9 7.9 402 35.4 Example 8 44.9 2385 7.2 10.6 7.7 50.4 9.1 487 54.2 Example 9 48.7 2517 8.8 4.9 1.5 28.3 7.4 399 36.8 Example 10 45.1 2326 8.1 5.6 1.9 39.6 6.8 410 44.5 Example 11 46.8 2472 7.4 11.2 7.9 45.3 11.8 493 49.7 Comparative Example 1 31.6 1764 4.2 39.5 — 66.8 18.6 1180 64.1 Comparative Example 2 46.9 2465 8.7 5.3 1.2 8.5 7.1 391 23.8 Comparative Example 3 34.8 1912 4.9 25.7 18.4 59.6 10.2 862 57.5 Comparative Example 4 47.1 2498 8.5 5.8 2.3 12.6 7.8 404 27.4 Comparative Example 5 52.4 2593 9.0 4.4 2.0 21.1 5.7 372 27.9 Comparative Example 6 36.7 2116 5.5 17.6 9.8 58.7 15.9 646 63.5 Comparative Example 7 39.5 1698 8.7 6.2 3.0 41.4 5.1 418 46.8 Comparative Example 8 38.2 3315 4.6 14.3 9.1 34.6 24.9 581 39.2 Comparative Example 9 38.9 2264 5.7 19.2 12.8 61.5 10.4 723 59.6 Comparative Example 10 50.3 2577 8.4 4.9 1.3 17.4 7.6 387 29.1 Comparative Example 11 39.6 2271 5.9 21.5 14.1 56.8 10.7 744 56.4 Comparative Example 12 48.9 2504 8.9 4.7 1.1 18.6 7.2 382 28.3 Comparative Example 13 37.8 2056 5.6 7.9 1.6 32.4 6.5 408 36.7 Comparative Example 14 40.7 2298 5.8 18.4 11.7 48.9 13.6 668 51.5 Comparative Example 15 35.9 2184 4.8 13.2 8.9 37.5 27.8 575 38.4
[0181] Experimental conclusions and analysis:
[0182] As shown in Table 1, Examples 1 to 11 all used polyester biodegradable resin, engineering support components, thermal history-responsive latent degradable particles, compatibility control components, and chain extension control components to form engineering particles. Furthermore, the thermal history-responsive latent degradable particles all included a hydrophilic biodegradable core material, a solid-phase breaking layer, and a melt shear buffer layer. The overall experimental data showed tensile strength ranging from 42.6 MPa to 51.2 MPa, flexural modulus ranging from 1845 MPa to 3192 MPa, and notched impact strength ranging from 5.8 kJ / m² to 9. The parameters of 1 kJ / m², MFR change rate of 4.8% to 11.2%, shell penetration damage rate of 1.5% to 7.9%, core material exposure ratio of 23.9% to 57.2%, direct contact area ratio of 5.4% to 16.1%, moisture content of 386 ppm to 512 ppm, and 45-day staged biodegradation rate of 31.5% to 61.3% indicate that within the composition and process range defined in the claims, the engineered particles can simultaneously maintain mechanical load-bearing capacity, processing stability, low moisture content, and post-disposal degradation initiation capability.
[0183] The tensile strength of Example 1 was 47.8 MPa, the flexural modulus was 2486 MPa, the notched impact strength was 8.4 kJ / m², the MFR change rate was 7.1%, the shell penetration failure rate was 3.2%, the core material exposure ratio was 43.5%, the direct contact area ratio was 8.6%, the water content was 430 ppm, and the 45-day stage biodegradation rate was 48.6%. The above data indicate that Example 1 achieved a relatively balanced state between engineering support, melt stability, and degradation initiation. There was no drastic fluctuation in melt performance due to premature exposure of the hydrophilic biodegradable core material, nor was there any difficulty in opening degradation channels after waste breakage due to over-coating.
[0184] Examples 2 and 3 are used to illustrate the effect of the amount of thermally history-responsive latent degradable particles on the performance balance. In Example 2, when the amount of thermally history-responsive latent degradable particles is at the lower limit, the tensile strength is 51.2 MPa, the notched impact strength is 8.9 kJ / m², and the MFR change rate is only 4.8%. This indicates that when the amount of hydrophilic degradable core material introduced is low, the integrity of the polyester continuous phase is good, and the processing stability and mechanical properties are high. However, the core material exposure ratio is only 24.7%, and the 45-day stage biodegradation rate is only 31.5%, indicating that the number of degradation initiation channels is relatively insufficient.
[0185] In Example 3, when the amount of thermal history-responsive latent degradation particles was at its upper limit, the core material exposure ratio increased to 55.8%, and the 45-day stage biodegradation rate increased to 61.3%, indicating that the hydrophilic channels increased significantly after waste crushing. However, the tensile strength decreased to 42.6 MPa, and the notched impact strength decreased to 6.7 kJ / m², indicating that too many thermal history-responsive latent degradation particles would occupy part of the continuous phase bearing space.
[0186] The above results indicate that the limit of 3 to 25 parts is not simply a conventional choice to increase the amount of degradable filler, but rather to create an acceptable window between engineering load and degradation initiation.
[0187] Comparative Examples 5 and 6 further demonstrate the rationality of the above dosage range. In Comparative Example 5, the dosage of thermally responsive latent degradation particles was lower than the protection range, the tensile strength reached 52.4 MPa, and the notched impact strength reached 9.0 kJ / m², but the core material exposure ratio was only 21.1%, and the 45-day stage biodegradation rate was only 27.9%, indicating that although the material has good mechanical properties, it is difficult to form a sufficient path for post-waste moisture to enter.
[0188] In Comparative Example 6, the amount of thermal history-responsive latent degradation particles was higher than the protection range. The biodegradation rate reached 63.5% in the 45-day stage, but the tensile strength decreased to 36.7 MPa, the notched impact strength decreased to 5.5 kJ / m², the MFR change rate increased to 17.6%, the shell penetration failure rate increased to 9.8%, and the water content increased to 646 ppm. This indicates that excessive hydrophilic latent particles will increase interface defects and processing thermal history damage, and make it difficult for the material to meet the stability required for engineering applications.
[0189] Examples 4 and 5 are used to illustrate the effect of the amount of engineering support components on the load-bearing capacity of the project. In Example 4, when the amount of engineering support components is at the lower limit, the flexural modulus is 1845 MPa and the notched impact strength is 9.1 kJ / m², indicating that the material has better toughness when the filler is less, but the rigid support is insufficient.
[0190] In Example 5, when the engineering support component is at its upper limit, the flexural modulus increases to 3192 MPa and the tensile strength increases to 50.5 MPa, indicating that the engineering support effect is enhanced. However, the notched impact strength decreases to 5.8 kJ / m², and the proportion of direct contact area increases to 16.1%, indicating that excessive filler can easily increase local rigidity concentration and the probability of interfacial contact.
[0191] In Comparative Example 7, the engineered support component was below the protection range, with a flexural modulus of only 1698 MPa and a tensile strength of only 39.5 MPa, indicating that insufficient engineered support directly weakens the dimensional stability and load-bearing capacity of the product. In Comparative Example 8, the engineered support component was above the protection range, with a flexural modulus of 3315 MPa, but the notched impact strength decreased to 4.6 kJ / m², the MFR change rate increased to 14.3%, the shell penetration failure rate increased to 9.1%, and the direct contact area ratio increased to 24.9%, indicating that excessive engineered support component would destroy the isolation and buffering effect of the polyester continuous relative thermal history responsive latent degradation particles.
[0192] Comparative Example 1 directly blended corn starch and microcrystalline cellulose into a polyester biodegradable resin. Its 45-day stage biodegradation rate reached 64.1%, and the core material exposure ratio reached 66.8%. However, the tensile strength was only 31.6 MPa, the flexural modulus was only 1764 MPa, the notched impact strength was only 4.2 kJ / m², the MFR change rate was as high as 39.5%, and the moisture content was as high as 1180 ppm. This indicates that although directly introducing hydrophilic biodegradable core material can improve early biodegradation performance, the cost is a significant increase in interface defects, moisture introduction, and polyester segment hydrolysis risk during the processing and service stages.
[0193] The above results indicate that the present invention does not simply rely on hydrophilic components to improve degradation performance, but rather uses a latent shell structure to postpone the action of the hydrophilic core material to the waste crushing stage.
[0194] Comparative Example 2 uses ordinary dense polyester single-layer coating of hydrophilic particles. Its tensile strength is 46.9 MPa, flexural modulus is 2465 MPa, notched impact strength is 8.7 kJ / m², MFR change rate is 5.3%, and moisture content is 391 ppm. This shows that ordinary dense coating can isolate the hydrophilic core material and maintain good molding stability during the processing stage. However, its core material exposure ratio is only 8.5%, and the 45-day stage biodegradation rate is only 23.8%, indicating that the dense coating layer is difficult to effectively open the moisture entry path after waste crushing.
[0195] The results show that simple coating cannot solve the contradiction between the isolation of the processing stage and the opening of the waste stage faced by the present invention. The combination of solid phase boundary layer and melt shear buffer layer is necessary.
[0196] Comparative Example 3, without a melt shear buffer layer, showed an increased shell penetration failure rate of 18.4%, an MFR change rate of 25.7%, a moisture content of 862 ppm, and decreased tensile strength and notched impact strength to 34.8 MPa and 4.9 kJ / m², respectively. This indicates that without a melt shear buffer layer, the solid-phase boundary layer is prone to premature penetration and rupture during melt granulation and secondary melt molding due to screw shearing, particle collision, and filler friction, causing premature exposure of the hydrophilic biodegradable core material and triggering interfacial water absorption and melt fluctuations.
[0197] Comparative Example 4, without a solid-phase boundary layer, had a shell penetration damage rate of 2.3% and an MFR change rate of 5.8%, exhibiting good mechanical properties. However, the core material exposure rate was only 12.6%, and the 45-day stage biodegradation rate was only 27.4%. This indicates that without a solid-phase boundary layer, the waste solid phase fragmentation is difficult to form an effective boundary opening, and the hydrophilic and biodegradable core material cannot be fully converted into water to enter the pathway.
[0198] The above two sets of comparisons prove that the melt shear buffer layer mainly solves the protection problem in the processing heat history, while the solid phase boundary breaking layer mainly solves the channel opening problem after waste crushing. The two are not ordinary coating structures that can be substituted for each other.
[0199] Examples 6 and 7 are used to illustrate the rationality of the solid-phase boundary layer thickness range. In Example 6, the solid-phase boundary layer thickness is 0.2 μm, the core material exposure ratio reaches 57.2%, and the 45-day stage biodegradation rate reaches 58.9%. However, the shell penetration damage rate is 7.3%, and the MFR change rate is 9.8%. This indicates that a thinner solid-phase boundary layer is beneficial for quickly opening channels after waste crushing, but the processing protection margin is small.
[0200] In Example 7, the solid-phase boundary layer thickness was 5.0 μm, the shell penetration failure rate was only 1.8%, and the MFR change rate was 5.2%, indicating strong processing protection. However, the core material exposure ratio decreased to 23.9%, and the 45-day stage biodegradation rate decreased to 35.4%.
[0201] In Comparative Example 9, the thickness of the solid-phase boundary layer was lower than the protection range, the shell penetration damage rate increased to 12.8%, the MFR change rate increased to 19.2%, and the moisture content increased to 723 ppm; in Comparative Example 10, the thickness of the solid-phase boundary layer was higher than the protection range, the core material exposure rate was only 17.4%, and the 45-day stage biodegradation rate was only 29.1%.
[0202] The above results demonstrate that a solid-phase boundary layer thickness of 0.2 μm to 5 μm can achieve a balance between resistance to penetrating fracture during the processing stage and the possibility of boundary breaking during the disposal stage.
[0203] Examples 8 and 9 are used to illustrate the rationality of the melt shear buffer layer thickness range. In Example 8, the melt shear buffer layer thickness is 0.5 μm, the shell penetration failure rate is 7.7%, the MFR change rate is 10.6%, the core material exposure ratio is 50.4%, and the 45-day stage biodegradation rate is 54.2%, indicating that a thinner buffer layer can still maintain a basic protective function, but its absorption capacity for shear and impact is close to the lower limit.
[0204] In Example 9, the melt shear buffer layer thickness was 8.0 μm, the shell penetration failure rate was reduced to 1.5%, and the MFR change rate was reduced to 4.9%, indicating good processing stability. However, the core material exposure ratio decreased to 28.3%, and the 45-day stage biodegradation rate decreased to 36.8%.
[0205] In Comparative Example 11, the thickness of the melt shear buffer layer was lower than the protection range, the shell penetration failure rate increased to 14.1%, the MFR change rate increased to 21.5%, and the moisture content increased to 744 ppm; in Comparative Example 12, the thickness of the melt shear buffer layer was higher than the protection range, the core material exposure rate was only 18.6%, and the 45-day stage biodegradation rate was only 28.3%.
[0206] The above results demonstrate that a thicker melt shear buffer layer is not necessarily better. If the thickness is too low, it will cause damage from the processing heat history, while if the thickness is too high, it will hinder the exposure of the core material after waste and crushing.
[0207] Examples 10 and 11 are used to illustrate the rationality of the unit mass mechanical energy input range in the low-damage mixing zone in the middle and later stages. In Example 10, the unit mass mechanical energy input is 35% of that in the front stage, the shell penetration damage rate is 1.9%, and the MFR change rate is 5.6%, indicating that the lower mixing strength can protect the shell. However, the tensile strength is 45.1 MPa and the flexural modulus is 2326 MPa, indicating that the dispersion effect is relatively weak.
[0208] In Example 11, the mechanical energy input per unit mass was 85% of that of the front section, the tensile strength was 46.8 MPa, the flexural modulus was 2472 MPa, and the core material exposure ratio was 45.3%. However, the shell penetration failure rate increased to 7.9%, and the MFR change rate increased to 11.2%, indicating that higher mixing strength is beneficial for dispersion, but it is close to the shell protection limit.
[0209] In Comparative Example 13, the mechanical energy input per unit mass was below the protection range, with a tensile strength of only 37.8 MPa, a flexural modulus of only 2056 MPa, and a notched impact strength of only 5.6 kJ / m². This indicates that insufficient mixing leads to inadequate dispersion of thermally responsive latent degradation particles and the formation of local defects. In Comparative Example 14, the mechanical energy input per unit mass was above the protection range, with the shell penetration failure rate increasing to 11.7%, the MFR change rate increasing to 18.4%, and the moisture content increasing to 668 ppm. This indicates that excessive mixing can damage the shell integrity.
[0210] The above results demonstrate that the mixing intensity in the middle and later stages needs to be matched with the shell structure of thermally responsive latent degradation particles, rather than simply increasing the screw shear to obtain better dispersion.
[0211] Comparative Example 15 added thermal history-responsive latent degradation particles and engineering support components simultaneously through the same main feed port. The direct contact area ratio reached 27.8%, which was significantly higher than 8.6% in Example 1. At the same time, the tensile strength decreased to 35.9 MPa, the notched impact strength decreased to 4.8 kJ / m², the MFR change rate increased to 13.2%, the shell penetration failure rate increased to 8.9%, the water content increased to 575 ppm, and the 45-day stage biodegradation rate was only 38.4%.
[0212] The results show that when the engineered support component and the thermally responsive latent degradable particles come into local contact and agglomerate before the formation of the polyester continuous melt, the rigid engineered support component will cause local wear and stress concentration on the shell of the latent degradable particles and weaken the isolation effect of the polyester continuous melt on the two, thus simultaneously affecting the processing stability, mechanical properties and post-disposal degradation initiation effect.
[0213] Based on the above embodiments and comparative examples, it can be seen that if hydrophilic biodegradable core material is added directly, although the phased biodegradation rate is relatively high, the processing stability and mechanical properties are significantly deteriorated; if ordinary dense coating is used, although the processing stability is better, the core material is not sufficiently exposed after disposal; if a melt shear buffer layer is lacking, the shell layer will break prematurely during the processing stage; if a solid-phase boundary breaking layer is lacking, it will be difficult to open the degradation channels after disposal and crushing; if the amount of engineering support components, thermal history-responsive latent degradation particles, or mid-to-late stage mixing strength exceeds the limit range, it will cause insufficient support, interface defects, shell layer damage, or insufficient degradation initiation, respectively.
[0214] The above results collectively demonstrate that the present invention establishes a time-separation mechanism for protection during the processing stage and activation during the waste stage by using a layered particle structure, a process sequence of forming a continuous polyester melt in the front stage followed by side feeding of latent degradation particles in the middle and rear stages, and controlling the direct contact area ratio between the engineering support components and the thermally responsive latent degradation particles.
[0215] The underlying mechanism of this invention is as follows: during the melt processing stage, the melt shear buffer layer absorbs shear and collision energy, keeping the solid phase boundary layer from breaking through and preventing the hydrophilic biodegradable core material from absorbing water prematurely or inducing hydrolysis of the polyester continuous phase; during the service stage, the engineering support component undertakes the functions of reinforcement and dimensional stability, and the wear of the engineering support component on latent degradable particles is reduced by isolating the polyester continuous phase; during the waste solid phase crushing stage, the solid phase boundary layer forms a boundary opening, exposing the hydrophilic biodegradable core material at the crushed surface and making it a path for water to enter.
[0216] Based on the preferred embodiments of the present invention described above, those skilled in the art can make various changes and modifications without departing from the inventive concept. The technical scope of this invention is not limited to the contents of the specification, but must be determined according to the scope of the claims.
Claims
1. An engineering granule of a polyester biodegradable plastic, characterized in that, By weight, it includes the following components: 100 parts of biodegradable polyester resin; The engineering support components consist of 5 to 35 parts; 3–25 parts of thermally history-responsive latent degradation particles; 0.5–8 parts of compatibility-regulating components; Chain expansion regulating component: 0.05–3 parts; The thermal history-responsive latent degradation particles include a hydrophilic degradable core material, a solid-phase boundary-breaking layer covering the outside of the hydrophilic degradable core material, and a melt shear buffer layer covering the outside of the solid-phase boundary-breaking layer. The melt shear buffer layer has deformation buffering properties at the melt processing temperature of the polyester biodegradable resin, so that the solid phase breaking layer remains unbroken during melt granulation and secondary melt molding. The solid-phase boundary breaking layer forms a boundary opening after solid-phase crushing treatment, exposing the hydrophilic and biodegradable core material at the fracture surface. Both the engineering support component and the thermal history-responsive latent degradable particles are dispersed in the continuous phase formed by the polyester biodegradable resin, and in the cross section of the engineering particles, the direct contact area between the engineering support component and the thermal history-responsive latent degradable particles accounts for 0 to 20% of the outer surface area of the thermal history-responsive latent degradable particles.
2. The engineered granules of a polyester biodegradable plastic according to claim 1, characterized in that, The polyester biodegradable resin includes at least two of polylactic acid, polybutylene adipate terephthalate, polybutylene succinate, and polyhydroxyalkanoates; by weight, the polyester biodegradable resin includes 40-75 parts of polylactic acid, 15-45 parts of polybutylene adipate terephthalate, and 5-30 parts of at least one of polybutylene succinate and polyhydroxyalkanoates.
3. The engineered granules of a polyester biodegradable plastic according to claim 1, characterized in that, The engineering support component includes at least one of talc, calcium carbonate, wollastonite, silica, montmorillonite, glass micron powder, and plant ash. The average particle size of the engineering support component is 0.5 to 15 μm, and the surface of the engineering support component has at least one of silane coupling layer, titanate coupling layer, aluminate coupling layer, and polyester oligomer compatibility layer.
4. The engineered granules of a polyester biodegradable plastic according to claim 1, characterized in that, The hydrophilic biodegradable core material includes at least one of starch, cellulose, hemicellulose, wood fiber, porous plant fiber particles, and biodegradable low-density polyester, and the average particle size of the hydrophilic biodegradable core material is 5 to 80 μm.
5. The engineering granules of a polyester biodegradable plastic according to claim 1, characterized in that, The solid-phase boundary-breaking layer includes at least one of a brittle polyester microlayer, a biodegradable layer containing mineral flakes, and a hydrolyzable brittle oligomer layer, and the thickness of the solid-phase boundary-breaking layer is 0.2 to 5 μm.
6. The engineered granules of a polyester biodegradable plastic according to claim 1, characterized in that, The melt shear buffer layer includes at least one of a flexible aliphatic polyester layer, a polyester grafted compatibility layer, and a biodegradable elastic phase layer. The thickness of the melt shear buffer layer is 0.5–8 μm, and the softening temperature of the melt shear buffer layer is 5–35 °C lower than that of the solid phase boundary layer.
7. The engineered granules of a polyester biodegradable plastic according to claim 1, characterized in that, After the engineering particles are melt-blended, the shell penetration damage rate of the thermally responsive latent degradable particles is 0-8%; after the products obtained by the engineering particles through secondary melt molding are subjected to solid-phase crushing treatment, the exposure ratio of the hydrophilic degradable core material on the crushed cross-section is 20%-60%.
8. The engineered granules of a polyester biodegradable plastic according to claim 1, characterized in that, The compatibility regulating component includes at least one of maleic anhydride-grafted polyester, epoxy functionalized compatibilizer, isocyanate functionalized compatibilizer, and polyester oligomer compatibilizer; the chain extension regulating component includes at least one of multifunctional epoxy chain extender, carbodiimide chain extender, isocyanate chain extender, and acid anhydride chain extender.
9. A method for preparing polyester biodegradable plastic engineering granules as described in any one of claims 1 to 8, characterized in that, Includes the following steps: S1. Prepare thermal history-responsive latent degradation particles, wherein the thermal history-responsive latent degradation particles include a hydrophilic degradable core material, a solid-phase boundary layer and a melt shear buffer layer, and the average particle size of the thermal history-responsive latent degradation particles is 10-120 μm. S2. Add the biodegradable polyester resin, engineering support component, compatibility control component and chain expansion control component to the front end of the extrusion equipment for melt compounding to form a continuous polyester melt containing the engineering support component; S3. After the continuous polyester melt is formed, the thermal history-responsive latent degradation particles are added to the later stage of the extrusion equipment. S4. Control the mixing intensity in the later stage of the extrusion equipment so that the thermal history-responsive latent degradation particles are dispersed in the continuous polyester melt, and the solid phase boundary layer remains unbroken during the melt mixing process. S5. After degassing, extrusion, cooling and pelletizing, the engineered granules of the polyester biodegradable plastic are obtained.
10. The method for preparing polyester biodegradable plastic engineering particles according to claim 9, characterized in that, In step S2, the temperature of the front section of the extrusion equipment is 150–210°C, and the screw speed is 150–450 r / min. In step S3, the thermal history-responsive latent degradation particles are added to the middle and rear sections of the extrusion equipment via side feeding. In step S4, the unit mass mechanical energy input of the middle and rear sections of the extrusion equipment is 35%–85% of the unit mass mechanical energy input of the front section of the extrusion equipment. The agglomerate size of the thermal history-responsive latent degradation particles is 20–200 μm, and the shell penetration breakage rate of the thermal history-responsive latent degradation particles after melt mixing is 0–8%. Step S5 is followed by a dehumidification, crystallization, and shaping step, which involves treating the granulated engineered particles at 45–85°C for 0.5–6 hours to achieve a moisture content of 100–800 ppm.